2008
DOI: 10.5488/cmp.11.1.7
|View full text |Cite|
|
Sign up to set email alerts
|

Inelastic neutron scattering applied to the investigation of collective excitations in topologically disordered matter

Abstract: Inelastic neutron scattering techniques are introduced here as one of the most important experimental techniques in the investigation of collective excitations in fluids (liquids and compressed gases) and amorphous solids. The correlation functions involved, the spectra of which are determined in inelastic neutron scattering experiments, the dispersion relations of the collective excitations and how they are obtained from the measured spectra and finally two of the most often used instrumental techniques are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Because of amorphous protein samples that lack a preferred orientation, it is not easy to explicitly differentiate between longitudinal and transverse acoustic modes. 26 , 39 , 44 However, the calculated values of low-frequency phonon-like excitations can be attributed to the transverse acoustic mode, which is in good agreement with recently published molecular dynamics simulations 45 and experiments. 30 , 46 , 47 Furthermore, for , an apparent softening of the localized intra-protein vibrations with an increase in temperature is observed, as indicated by the decrease in the excitation energy in both samples, whereas the acoustic mode is nearly temperature independent.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Because of amorphous protein samples that lack a preferred orientation, it is not easy to explicitly differentiate between longitudinal and transverse acoustic modes. 26 , 39 , 44 However, the calculated values of low-frequency phonon-like excitations can be attributed to the transverse acoustic mode, which is in good agreement with recently published molecular dynamics simulations 45 and experiments. 30 , 46 , 47 Furthermore, for , an apparent softening of the localized intra-protein vibrations with an increase in temperature is observed, as indicated by the decrease in the excitation energy in both samples, whereas the acoustic mode is nearly temperature independent.…”
Section: Resultssupporting
confidence: 89%
“…The dispersion curves overlaid on top of 2-dimensional (2D) raw INS spectra for dGFP samples at T = 150 K and Q = 0.64 Å −1 confirm that the calculated excitation energies are larger than the instrumental resolution ( Figures 2 C and 2D). Furthermore, the bending of the energy dispersion curve occurs at the boundary of the acoustic branch (i.e., Q m ∼ 1.1 Å −1 ), suggesting the existence of a pseudo-Brillouin zone 26 with a finite group velocity up to the value of Q m , after which a plateau develops or starts to deviate from the usual Q dependence. The value of Å −1 corresponds to the topological disorder length scale in the sample or half of the distance to the nearest pseudo-reciprocal lattice point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inelastic X-ray scattering (IXS) technique is a unique tool to study the collective density fluctuations in amorphous materials, glasses, or liquids. High energy resolution of the order of milli-electronvolt (meV) achieved by IXS spectrometers allows a precise investigation of highly damped collective modes and the phonon dispersion in topologically disordered systems. Previously, there are evidence from inelastic neutron scattering (INS) experiments of collective motions in proteins, which are similar to the boson peak in the glass-forming liquids due to the collective excitations or density fluctuations. Furthermore, IXS, INS, Brillouin neutron spectroscopy (BNS), and molecular dynamic (MD) simulations have revealed the propagation of acoustic phonons in proteins and their hydration water in the longer wavelength limit corresponding to the length scale larger than ∼ 1 nm. However, very few studies reported investigation of local excitations within the protein secondary structure on a scale shorter than 1.5 nm. ,,, A recent IXS experiment by Wang et al has studied the collective excitations in a globular protein lysozyme and concluded that the phonon energy softening and phonon population enhancement in hydrated protein (both native and denatured) is induced by the hydration shell . On the other hand, MD simulation results clearly suggested that the strong coupling between the dynamics of a globular protein, such as maltose binding protein and its hydration shell, exists rather than protein dynamics being slaved to the hydration water .…”
Section: Introductionmentioning
confidence: 99%
“…full circles -the experimental data of Copley and Rowe [11], vertical bars -the experimental data of Glaeser et al [12], solid curve -the numerical calculation of the dispersion equation [13].…”
mentioning
confidence: 99%